Dietetic practices in adult hemodialysis units compared to k/doqi guidelines, lebanon - mirey karavetian; nanne de vries; hafez elzein (The Korean Society of Nephrology, 2012)
Hospitals in Lebanon mostly employ only one dietitian to conduct all dietetic/food service/administrative tasks including hemodialysis (HD) units which are exclusively hospital based. Little is known about dietetic practices in these (HD) units. Kidney Disease Outcomes Quality Initiative (KDOQI) and American Dietetic Association (ADA) presented evidence that the presence of a competent dietitian in the HD unit has benefits on HD patient's health and quality of life and is cost effective. This study aimed to reveal the current practices provided by dietitians to HD patients in Lebanon compared to KDOQI nutrition guidelines. A 36 item anonymous self-administered questionnaire was sent to all HD units in Lebanon (n=55). The questionnaire included 2 sections: 1) demographics and professional characteristics; 2) routine clinical practice Thirty eight (69%) of the dietitians responded; only 34 were of use. The questions in survey were categorical, thus only the answers with the majority of the respondents will be reported: 97% were female. 82% were within the age of 21-34, 62% had 3-10 years in clinical practice and 44% had only 0-2 years exposure to renal patients. Most dietitians (69%) worked in hospitals with 50-150 inpatients and 26-75 HD patients. Sixty nine percent of dietitians spent more than 36 hours per week in the hospital, while 85% spent less than 10 hours per week in the HD unit. As to the level of applying KDOQI nutrition guidelines in routine practice, of the 23 guidelines asked, all dietitians used at least 1 guideline, 17% used 5 and 23% used 10 guidelines. Only one dietitian applied all guidelines. A total compliance to guidelines score was developed as a percentage of total compliance which showed 37±15.51% (min14, max 73). Barriers identified were lack of time and lack of integration into the medical team. It is evident that dietetic practices in Lebanon targeting HD patients need support in all aspects: time, knowledge, empowerment and training.